Factors Affecting Internal Auditor Performance: The Moderation Role of Papuan Culture-Based Development - Seralurin, Yohanes Cores; Allolayuk, Paulus K.; Noch, Muhamad Yamin; Pattiasina, Victor; Tamaela, Eduard Yahannis (Universitas Negeri Malang, 2022)
This study aimed to analyze the impact of locus of control, task complexity, and organizational commitment on internal auditor performance. The population of this study included all auditors at 4 (four) Inspectorate Offices in Papua Province (Jayapura City, Jayapura Regency, Keerom Regency, and Sarmi Regency). The research samples were collected using a purposive sampling technique. The collected data were the processed using the Moderated Regression Analysis (MRA) technique. The results showed that locus of control had a significant effect on inspectorate internal auditor performance. Task complexity had a negative effect on internal auditor performance. Organizational commitment did not affect internal auditor performance. Papuan culture-based development moderated the effect of locus of control on internal auditor performance. Papuan culture-based development did not moderate the effect of task complexity on internal auditor performance, and traditional Papuan culture based-development did not moderate the effect of organizational commitment on internal auditor performance. The finding implied that locus of control affected auditor performance, while tax complexity and organizational commitment did not affect auditor performance